2004
DOI: 10.1126/science.1099961
|View full text |Cite
|
Sign up to set email alerts
|

A Network of Control Mediated by Regulator of Calcium/Calmodulin-Dependent Signaling

Abstract: Calmodulin (CaM) is a major effector for the intracellular actions of Ca2+ in nearly all cell types. We identified a CaM-binding protein, designated regulator of calmodulin signaling (RCS). G protein-coupled receptor (GPCR)-dependent activation of protein kinase A (PKA) led to phosphorylation of RCS at Ser55 and increased its binding to CaM. Phospho-RCS acted as a competitive inhibitor of CaM-dependent enzymes, including protein phosphatase 2B (PP2B, also called calcineurin). Increasing RCS phosphorylation blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
101
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 22 publications
2
101
0
1
Order By: Relevance
“…With regard to miR-128b, it is highly expressed in the frontal cortex and its host gene, regulator of calmodulin signaling (RCS), is essential for mediating dopamine transmission 9 , which in the ILPFC has been shown to be critical for the formation of fear extinction memories 10 . After auditory cued fear conditioning (3 tone-shock pairings) in a standard conditioning chamber (Context A) on day 1, mice were either exposed to a novel context (Context B) for 2 hours (FC-No EXT) or exposed to a strong extinction protocol (EXT, 60 non-reinforced tone exposures (CS) in order to induce complete extinction) in context B.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to miR-128b, it is highly expressed in the frontal cortex and its host gene, regulator of calmodulin signaling (RCS), is essential for mediating dopamine transmission 9 , which in the ILPFC has been shown to be critical for the formation of fear extinction memories 10 . After auditory cued fear conditioning (3 tone-shock pairings) in a standard conditioning chamber (Context A) on day 1, mice were either exposed to a novel context (Context B) for 2 hours (FC-No EXT) or exposed to a strong extinction protocol (EXT, 60 non-reinforced tone exposures (CS) in order to induce complete extinction) in context B.…”
Section: Resultsmentioning
confidence: 99%
“…miR-128-2 is an intragenic miRNA located within the 18th intron of ARPP21 gene. 30 The analysis of ARPP21 gene expression evidences that ARPP21 mRNA is induced, to a similar extent than that of miR-128-2, following mutant p53His175 expression (Figure 1e and Supplementary Figure 1B). Altogether, these findings indicate that mutant p53 protein controls the expression of both miR-128-2 and ARPP21 through a common transcriptional regulatory mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…PKA-dependent phosphorylation of receptors, ion channels, transcription factors, and other proteins accounts for much of the structural and functional plasticity regulated by dopamine (2). Our previous studies that identified and characterized targets of the cAMP/PKA pathway have been critical for understanding the actions of dopamine in MSNs (3,4). For example, the PKA substrate, dopamine and cAMP-regulated phosphoprotein, M r 32 kDa (DARPP-32) has been extensively analyzed and found to amplify dopamine action in MSNs through inhibition of protein phosphatase-1 (PP1).…”
mentioning
confidence: 99%